The president in Lithuanian political system: Search for position and power - Alvidas Lukošaitis (Politologija)
Appeal of the Government to the Constitutional Court dated December 17, 1997, was aimed at judging whether the ruling of Seimas „On the Agenda of the Government of the Republic of Lithuania" dated December 10, 1997, went in no counteraction to the Constitution of the Republic of Lithuania. This appeal portrayed ambiguousness, which exists in relations between the legislative (Seimas) and the executive (President and Government) branches of Government. Ruling of the Constitutional Court January 10, 1998, interprets and rationalises, first, some of the Constitutional norms and, second, delineates guises of the political situation, which have crystallised in the aftermath of the elections.